PERFORMANCE ANALYSIS OF MC-DS-CDMA WIRELESS COMMUNICATIONS OVER RAYLEIGH FADING USING MAXIMAL RATIO COMBINING DIVERSITY TECHNIQUE - Jahid, Abu; Hossain, Md. Sanwar (European Scientific Journal, ESJ, 2015)
Multi carrier direct sequence code division multiple access (MC-DSCDMA) becomes a promising technique to support multiple users with secured high speed wireless communications as it capable to improve the system performance by mitigating inter-symbol interference (ISI). In this paper, MC-DS-CDMA with binary phase shift modulation (BPSK) scheme over Rayleigh and AWGN fading channel has been studied. An analytical approach is developed to find out the expressions of signal to interference plus noise ratio (SINR) as well as BER with maximal ratio combining (MRC) in the presence of multi-access interference (MAI). The system performance are evaluated in terms of SINR and BER by varying number of multiple users, fading parameter, number of subcarriers using MATLAB simulation. It is found that, the system performance highly deteriorated due to multipath fading. Optimum value of system parameters and receiver diversity technique improves the system performance significantly.